Associated factors study into the belated screening for leprosy in Benin - JOHNSON, ROCH CHRISTIAN; SOPOH, GHISLAIN E. (My University, 2022)
Leprosy is one of the neglected tropical diseases that manifests itself by a cutaneous and neurological attack whose evolution in the absence of an early detection and management is inevitably towards an acquired handicap. This handicap is responsible for significant physical, psychological and socio-economic suffering which alters the quality of life of the patient. In Benin, the epidemiological profile of leprosy is marked by a high and increasing proportion of new cases of leprosy with grade 2 disability and a high proportion of multibacillary leprosy cases. These indicators are markers of late detection of leprosy. In view of the new objectives of the new roadmap developed by WHO for the period 2021–2030, leprosy control remains a major health challenge for the actors of the epidemiological surveillance system. It is for this reason that we undertook this study to better understand the factors responsible for the late detection of leprosy in our country in order to propose relevant and innovative strategies and interventions to achieve the objectives of the WHO roadmap and also to participate in the improvement of the quality of life of leprosy patients. Our approach is motivated by the ambition to improve the health status of people affected by neglected tropical diseases, in this case leprosy.
Keywords: Leprosy; epidemiological profile; late detection; health statuts; Benin